“Internal emigration”: features of everyday behavior in the conditions of war - Вячеслав Попов (Cхід, 2022)
The article reconstructs the everyday life of urban dwellers during the revolution and civil war of 1917-1920 in Ukraine. Average people include representatives of different social groups of the urban population, united by the desire to ensure their own survival by adapting to changing political and economic realities. The main models of daily practices common at that time are considered, which include a change in appearance, the use of fake documents, maximum isolation, previously unusual activities, as well as masking genuine activities in case of their forbidden nature. Appearance changed mainly by abandoning the usual clothes which made it possible to determine the social status of its wearer. The registration of all kinds of certificates transferred their owners to the “socially close” groups of the new government, and was intended to save them from various persecutions. Isolation was achieved either by a regular change of place of residence, or by the complete avoidance of any contact. The greatest ability to externally reformat their former employment was demonstrated by professional traders who tried to remain faithful to their usual business, despite all the new restrictions. The author revealed that a characteristic feature of the life of specialists who had professions in demand under any government was the long-term preservation of their usual way of life, home comfort and contentment. The specific features of the general socio-anthropological crisis of this period have been established. Separately, the article discusses the practice of mental relaxation of citizens to preserve their illusory "small world", creating a simulation of a forever lost way of life around themselves or in the immediate environment. The author showed the consequences of applying such practices. The study of historical experience associated with periods of social uncertainty is relevant since real politics should consider the peculiarities of citizens' everyday behavior, which are mainly identical to the practices of the last century.